Pediatric Nephrotic Syndrome; Clinical Characteristics and Nutritional Status - Ali Ateia Elmabsout; Hajir Omar Tawfeeq; Jebril Elabidi (مجلة المختار للعلوم, 2020)
Nephrotic syndrome (NS), is the most common chronic renal disorder in children, with multifactorial risk factors and complex etiology. Therefore, the aim of the present study was to determine the age and gender distribution and also determine the clinical characteristics and nutritional status of pediatric nephrotic syndrome. A total of 75 patients with nephrotic syndrome series were selected through semi-constructed questionnaires. The age of our subjects ranged between 1-18 years. Body weight and height were extracted from patient files or self-reported to calculate BMI percentile. Laboratory tests such as blood glucose, lipid profile vitamin D, and HbA1C were included. All samples were analyzed through either mean ±SEM or Chi-square for determining significant differences. The present study showed that 75 patients were diagnosed as nephrotic syndrome. The average age of patients was 9 years old and the age which showed significance was 6-10 years (p=0.04). In comparison to females, males were highly significant (p=0.000). Blood biochemistry showed low levels of total protein, albumin, hemoglobin, HCT, MCV, WBC, (gran %), calcium and sodium, and high levels for lymphocyte (mid %), urea, creatinine, ESR, potassium, hematuria, serum cholesterol, TG and VLDL. All patients were diagnosed as idiopathic nephrotic syndrome. Low birth weight showed significant increase in nephrotic diseases (p<0.05). Nutritional indices showed high body weight status with more junk and nutritious foods consumed among nephrotic patients. The present study revealed that nephrotic syndrome significantly increased in males (p<0.05) and male to female ratio 2.6:1. It also showed that the age groups between 6-10 years are more prone to suffer from a nephrotic disease (p<0.05). A history of low birth weight in infants or child family ranking were shown to be risk factors contributing to nephrotic disease (p=0.000).